Cross-Cultural Awareness: EFL Learners’ Barriers to Learning English - Martin Kustati; Besral Besral; Teuku Zulfikar; Nurhamsi Deswila (Yayasan Keluarga Guru Mandiri, 2023)
When one learns a certain language, he/she should also learn its culture. This is because languages and cultures are integrated.Â For example, to acquire meanings, language students need to understand the culture of the language they are learning. This study seeks to determine the challenges faced by English language learners in understanding Islamic beliefs and western cultures. This was a descriptive qualitative study that utilized semi-structured interviews to acquire data. Interviews were conducted with eight pupils from the Islamic boarding school Ar-Risalah in West Sumatra. The result of interviews showed that the majority of learners acknowledged that they experienced cross-cultural hurdles in English learning because of being culturally insensitive, misunderstanding of cultural contents in the language materials, and formal intervention regarding the textbook. Students are confused to differentiate cultures shared by Islamic values and Western cultures as those Islamic values are not vividly depicted in English textbooks. Therefore, students have difficulties understanding English. It is imperative that future research investigate this topic, since culture and language are inseparable, in which people learning a certain language are also required to learn its culture.